2022
DOI: 10.1002/cptc.202200168
|View full text |Cite
|
Sign up to set email alerts
|

Aggregation Induced Emission (AIE)‐Active Poly(acrylates) for Electrofluorochromic Detection of Nitroaromatic Compounds

Abstract: Two aggregation induced emission (AIE)-active poly(acrylates) bearing triphenylvinyl-functionalized phenylcarbazole and triphenylamine pendants, respectively, were synthesized. Their fluorescence response to nitroaromatics and electrofluorochromic (EFC) properties were studied, whereby both the presence of nitroaromatics and applied voltages led to fluorescence quenching. In a very first attempt to perform EFC detection of nitroaromatics, it was surprisingly found that after initial fluorescence quenching, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…The rapid detection of explosives has always been of paramount importance due to national security, and the development of fluorescent explosive sensors has circumvented the need for time-consuming and costly routine instrumental analysis. Nitroaromatic explosives such as trinitrotoluene and picric acid are commonly detected by AIE-active polymers in the forms of highly emissive nanoaggregate solutions, thin films, or paper probes via photoinduced electron transfer (PET) fluorescence quenching. Previously, Tang et al prepared AIE-active nanosheets with approximately 7.0 nm thickness by crystallization of a poly­(ε-carprolactone) (PCL) terminated with two TPE moieties ( 15 ), which interestingly led to the TPE moieties pointing out, dangling on the surfaces of the lamellar structures (Figure a1) . The blue-emissive nanosheets were found to selectively sense picric acid among other nitroaromatics via fluorescence quenching with a Stern–Volmer constant of 380,000 L/mol (Figure a2).…”
Section: Aie-based Nanomaterials For Sensingmentioning
confidence: 99%
“…The rapid detection of explosives has always been of paramount importance due to national security, and the development of fluorescent explosive sensors has circumvented the need for time-consuming and costly routine instrumental analysis. Nitroaromatic explosives such as trinitrotoluene and picric acid are commonly detected by AIE-active polymers in the forms of highly emissive nanoaggregate solutions, thin films, or paper probes via photoinduced electron transfer (PET) fluorescence quenching. Previously, Tang et al prepared AIE-active nanosheets with approximately 7.0 nm thickness by crystallization of a poly­(ε-carprolactone) (PCL) terminated with two TPE moieties ( 15 ), which interestingly led to the TPE moieties pointing out, dangling on the surfaces of the lamellar structures (Figure a1) . The blue-emissive nanosheets were found to selectively sense picric acid among other nitroaromatics via fluorescence quenching with a Stern–Volmer constant of 380,000 L/mol (Figure a2).…”
Section: Aie-based Nanomaterials For Sensingmentioning
confidence: 99%
“…Through the use of multiple non-covalent binding motifs, these polymers are often capable of exhibiting reversible responsiveness to a myriad of stimuli. [227][228][229] For example, Jiang et al reported a stable supramolecular polymer containing tripodal pillar [5]arene tails. This supramolecular polymer can undergo reversible gel-sol transition via pH, thermal, and force stimuli and demonstrate strong AIE after gelation (Figure 28b).…”
Section: Multi-stimuli-responsive Structure Switchmentioning
confidence: 99%
“…Xiong and coworkers employed a novel AIE luminogen to design an organic multi-stimuli responsive fluorescent material. 228,232 Consisting of vinylpyridine motifs on a tetraphenylethene backbone, the AIE luminogen displayed reversible fluorescence under varying force, pH, and temperature stimuli. Due to the supramolecular intermolecular interactions as well as the presence of shrinkable space in the polymer's packing structure, the material can sustain fluorescence emission even under external pressure as high as 11.25 GPa.…”
Section: Multi-stimuli-responsive Structure Switchmentioning
confidence: 99%
“…361 More recently, in a follow-up of a previous work on AIE luminogens, 362 Chua and Xu et al synthesized AIE-active polyacrylates ( D21 ) bearing triphenylvinyl-functionalized triphenylamine and phenylcarbazole pendants with green and blue fluorescence, respectively. 52 While the presence of NACs led to fluorescence quenching of D21 due to PET, the application of voltage unexpectedly “turn-on” the fluorescence. The design of TPE-containing amphiphilic block copolymers ( D22 ) was investigated.…”
Section: Sensing For National Securitymentioning
confidence: 99%
“…The discovery of AIE phenomena has therefore revolutionized the fundamental concept of photoluminescence properties of materials, and how their high photoluminescent quantum yield (PLQY) in solid and aggregated states may allow them to be exploited in real life applications and state-of-the art technologies. In addition to chemical sensing, AIEgens can be exploited for biomedical applications such as biosensing, bioimaging and theranostics, [36][37][38][39][40][41][42] in optoelectronics for LED, photovoltaics, and electrofluorochrome applications, [43][44][45][46][47][48][49][50][51][52] as well as stimuli-responsive materials. 53 To date, a large number of AIE-based fluorescent probes have been reported, for the detection of a wide range of analytes including metal and inorganic ions, small molecules, macromolecules, enzymes and peptides.…”
Section: Introductionmentioning
confidence: 99%